2017
DOI: 10.1038/s41598-017-15681-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical switching current density induced by spin Hall effect in magnetic structures with first- and second-order perpendicular magnetic anisotropy

Abstract: In this study, we derive analytical expressions for the critical switching current density induced by spin Hall effect in magnetic structures with the first- and second-order perpendicular magnetic anisotropy. We confirm the validity of the expressions by comparing the analytical results with those obtained from a macrospin simulation. Moreover, we find that for a particular thermal stability parameter, the switching current density can be minimized for a slightly positive second-order perpendicular magnetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[5][6][7] The critical switching current density and charge-to-spin conversion efficiency are dependent on the PMA in the HM/FM system. [8,9] PMA of thin films can be affected by various techniques: thermal annealing, ion irradiation, or oxidation. [10][11][12][13][14][15][16][17] In the previous works, these methods all need an additional process after the thin films growth to modify PMA.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The critical switching current density and charge-to-spin conversion efficiency are dependent on the PMA in the HM/FM system. [8,9] PMA of thin films can be affected by various techniques: thermal annealing, ion irradiation, or oxidation. [10][11][12][13][14][15][16][17] In the previous works, these methods all need an additional process after the thin films growth to modify PMA.…”
Section: Introductionmentioning
confidence: 99%
“…Mn 3 Ge with its high magnetic anisotropy and lower mag netization could emit even higher frequencies in the THz range than Mn 3 Ga [16], especially if a similar magnetic compensa tion state can be realized. In addition, the critical switching current of magnetic tunnel junctions (MTJs) is also reduced with reduction of magnetization [21,22]. You et al [23] have shown via ab initio density functional calculations that such a magnetic compensation state can be achieved in the D0 22 Mn 3 Ge system by replacing part of the Mnatoms with either nickel, platinum, or palladium.…”
Section: Introductionmentioning
confidence: 99%
“…where θ is the polar angle of magnetization unit vector, and K 1 and K 2 are the firstand the second-order MA coefficients, respectively. Recent experimental [15][16][17][18][19][20] and theoretical [21][22][23][24][25][26] studies revealed the important properties of K 19) In this paper, we calculate K 1 and K 2 of Fe atomic monolayers (MLs) on the MgO(001) substrate under electric fields by using first-principles calculations based on fullrelativistic self-consistent calculations. The dependence of the thickness of the Fe layer on K 1 and K 2 was studied by varying the number of Fe MLs from one to four.…”
mentioning
confidence: 99%